Politische Bildung und Erziehung im Unterricht Kontrastive Fallstudien anhand von Videoaufzeichnungen politischen Fachunterrichts in Ost-, West- und Gesamtberlin von 1978 bis 1993 - Jehle, May (Dokumentarische Schulforschung, 2022)
The case studies are a systematizing comparative study of historical video recordings of political education in East, West, and all of Berlin from the period 1978 to 1993. Using ethnomethodological reconstructions, the conceptions and teaching practices within the various political contexts are analyzed and case-specific logics and cross-case contexts are discussed. The study follows the guiding intention of a more precise determination of possibilities and limits of political education and upbringing in subject teaching with a view to selected, also normative, points of reference. In the sense of a historical source critique, the specific visual stagings of pedagogical practice are also analyzed and discussed in the context of their origins and uses.